Metal‐Assisted One‐Pot Synthesis of Isoporphyrin Complexes. Issue 34 (15th July 2016) - Schweyen, Peter; Hoffmann, Martin; Krumsieck, Jens; Wolfram, Benedikt; Xie, Xiulan; Bröring, Martin
Abstract: Zinc and cadmium complexes of meso ‐arylisoporphyrins carrying a pyrrolyl or dipyrrinyl substituent at the sp 3 carbon atom were obtained through a simple one‐pot variation of the Alder–Longo porphyrin synthesis. Key to the formation and stabilization of isoporphyrins is the presence of metal acetates during the oxidative macrocyclization step. The characteristic Q‐bands of isoporphyrins are found in the NIR region between 750 nm and 880 nm. All of the isolated pyrrolyl‐ and dipyrrinyl‐appended isoporphyrins are stable under typical laboratory conditions and allow chemical transformations like BF2 coordination, transmetalation, and ligand exchange. Abstract : Old synthesis, new tricks : Isoporphyrins form in unprecedented amounts if the long‐established Adler–Longo condensation for tetraarylporphyrin synthesis is performed in the presence of metal acetates as template agents. The isoporphyrins formed by this one‐pot method are surprisingly stable and show the anticipated long‐wavelength absorption typical for this class of porphyrinoids.